A Microwave System For The Acid Dissolution Of Metal And Mineral Samples - S. A. Matthes (The National Institute for Occupational Safety and Health (NIOSH), 1983)
This Bureau of Mines report describes a system for the dissolution of metal and mineral samples using a microwave heat source. Samples and an acid mixture are placed in sealed polycarbonate vessels. The vessel contents are heated using microwaves, digested for 2 min, and quickly cooled. After the solution is brought to a final volume, the vessel contents are heated an additional 2 min in the microwave oven. Using this method, a slag, a feldspar, and a Ni-Cu alloy were dissolved and analyzed by atomic absorption spectroscopy. Values obtained for Na, K, Cu, Ni, Si, Mg, Mn, Ca, Al, and Fe agreed with certified values and had an average relative standard deviation of 1 pct. This system results in a significant savings in time and expense over traditional methods of sample dissolution, and is ideal for preparing solutions for analysis by atomic absorption, plasma optical emission, or X-ray spectroscopy.